Prehospital Scheduling Management by the Critical Path Method for Burn Mass Casualty Incidents - Chih-Peng Wang MS; Ban-Jwu Shih PhD; Shiumn-Jen Liaw MD (SAGE Publishing, 2021)
In 2015, a dust explosion occurred in New Taipei Water Park in Taiwan, and 499 casualties was appallingly high. In fact, the government spent 208 min of response time from receiving calls for emergency to sending the last wounded person to hospital. To stop a similar accident happening again, a well-prepared strategy, with an aim to reduce the rescue time, to respond to such an emergency is necessary. This study mainly focuses on the execution of mass casualty operations while both efficiency and quality of care are considered. We not only find that there is only 1 h or less to allocate rescue resources after a Burn Mass Casualty Incident (BMCI) happens but also shorten the response time. It is our first time to use a special method, called Critical Path Method (CPM), to analyze the rescue process. But before CPM is created, the benefit of available resources should be maximized, and timely, safe, and effective emergency medical services should be provided. With CPM, the interrelations of every activity can be visualized, and the most time-consuming activity can be found by this efficient time management. If the relationship between the predecessors and its successors operations of the most time-consuming activity item is reshaped, BMCI prehospital scheduling management becomes more effective based on its efficiency and quality of care.